PRODUCTION OF OXALIC ACID BY ASPERGILLUS NIGER - Sri Handayani; Suratman Suratman (Puslitbang tekMIRA, 2009)
Oxalic acid has been suggested to be essential in the metal leaching processes by Aspergillus niger. The ability of Aspergillus niger strain to produce a high amount of oxalic acid on glucose and sucrose media was investigated. The experimental results show that glucose is favorable for oxalic acid biosynthesis which can produce 14.47 g/L oxalic acid compared to 7.09 g/L oxalic acid on sucrose medium. The production pattern, however, were identical on both substrates. The main drawback of this fermentation was the low yield attained (75.47 % from theoretical yield) probably because some of glucose was oxidized to gluconic acid at the beginning of fermentation, and due to some limitation of growing the A. niger in shake flask condition because pH of the culture cannot be fully controlled in shake flask system. Therefore, batch culture in fully controlled fermentor can be carried out as further steps of experiment after shake flask.